A Rare Case of Adrenocortical Carcinoma (BIRDEM Medical Journal, 2013)
A 15 year old girl was admitted with absence of menstruation and increase growth of facial and body hair for two years along with change of voice for six months. With these complaint, tablet progesterone was advised but there was no withdrawal bleeding. On examination she had hirsuitism. She had normal female secondary sex characteristics with mild clitoromegaly. Her investigations revealed hyperandrogenemia with normal level of other adrenal hormones. Imaging revealed left adrenal mass. Left adrenalectomy done and histopathology revealed malignant tumor of Zona reticularis. Adrenocortical carcinoma is a rare tumor and only limited information is available about its natural history and the effects of therapy. The case is a rare androgen producing malignant tumor of adrenal having an earlier age of presentation. Birdem Med J 2013; 3(2): 110-112 DOI: http://dx.doi.org/10.3329/birdem.v3i2.17216